Phenology of Spondias tuberosa Arruda (Anacardiaceae) under different landscape management regimes and a proposal for a rapid phenological diagnosis using local knowledge - Neto Ernani MF Lins; Almeida Alyson LS; Peroni Nivaldo; Castro Cibele C; Albuquerque Ulysses P (BMC, 2013)
Abstract Background Studies aimed at investigating the influence of habitat change on species phenology. Studies that investigate people's perceptions of the phenology of certain species still area few; yet this approach is important for effective decision-making for conservation. The aim of this study was to investigate the phenology of Spondias tuberosa Arruda (Anacardiaceae), a native species of economic and ecological importance in northeastern Brazil, in five landscape units (LUs) (Mountain, Mountain Base, Pasture, Cultivated Areas and Homegardens) of a Caatinga region in Altinho, Pernambuco, northeastern Brazil. These data could then be compared with local people's perceptions of the species' phenophases. Method Collection of phenological data was carried out monthly from February 2007 to January 2009 and included activity, intensity and synchronization of reproductive and vegetative phenophases. Ethnobotanical data were gathered using a collaborative approach to access local people's knowledge about the species' phenological schedule. Results There were no significant differences in the intensity of phenophases among LUs, and there was a correspondence between people's perception of phenophases and the phenological data collected. The data show that the different management practices for LUs did not influence the phenology of the species. Conclusion The main conclusion of this study is the use of traditional knowledge as interesting tool for rapid phenological diagnosis. However further studies need to be developed to test this tool in other environments and cultural contexts.